The presented case study aims to demonstrate the efficacy of psychotherapy with a child previously treated with medication - Cheesman, C (Rhodes University, Faculty of Humanities, Department of Psychology, 1988)
The impetus for using the therapy with J.B. for this study was primarily the challenge inherent in the situation from the moment the parents and J.B. arrived for their family interview and assessment. They had been through many professionals by then, and much medication. They were sceptical of our intervention, since nothing to date had relieved the situation, and J.B. still had outbursts of rage towards his mother, he was still expressing suicidal ideation and anxiety. The challenge was particularly in relation to the mother, who had great difficulty conceptualising J.B. 's problems as being emotional and relational in nature - she was infinitely more comfortable with physiological interpretations of everything. This had the effect on the therapist and the supervisor of frequently reassuring their belief in psychotherapy as the treatment of choice in this case, or if in fact there was a lurking 'disease ' or organic cause to the child's behaviour. The pressure was thus considerable in this respect, despite the fact that the child had been examined physically and nothing found. This study aims to demonstrate the efficacy of psychotherapy, and the changes that took place, with this patient who was previously treated with medication.
Keywords: Child psychotherapy